The Study of Sasak Baby Care in Sade Village Cental Lombok - Resma Febriana, Lale Lorajita; Sugiyo Pranoto, Yuli Kurniawati (Jurusan PGPAUD FIP UNNES, 2018)
Baby care which is done from the birth age is very influential on its development and growth. Baby care in each region certainly has its own uniqueness based on with the beliefs and culture of the local community. Based on this, this research is carried out to describe how baby care by the Sasak tribe community in Sade Village, Central Lombok as one of the Tribes in Indonesia. Culture and trust in baby care is one of the things that influence children's development and growth. This study uses qualitative research method with the type of ethnographic research on the Sasak tribe in the Sade Village, Central Lombok. Data collection in this study includes interviews, observation, and documentation. Interview respondents in this study were 7 people, including village chief, village midwife, belian (shaman), and 4 people of the Sasak tribe community in Sade Village. The baby care which is carried out by the Sasak people in Sade Village is still done traditionally (merereng) yet still receives modern baby care techniques. Baby care is carried out from generation to generation based on the culture of the local community. The Sasak tribe in the Sade village of still believes in the role of belian (shaman) in the care of babies. There are restrictions and recommendations that are trusted by the Sasak tribe in the Sade village, in the form of restrictions for mothers and babies.